Security threats and measures in the Internet of Things for smart city infrastructure: A state of art - Sharma, Rohit; Arya, Rajeev (Transactions on emerging telecommunications technologies, 2023)
The Internet of Things (IoT) is a network of physical objects or “things” implanted with electronics, software, sensors, and connectivity to allow them to exchange data with servers, centralized systems, and other connected devices using several communication systems. IoT data is assembled from various sensors, nodes, and collectors and sent to the cloud. It is the most reliable framework for improving the quality and comfort of human life. It has made a substantial contribution to a wide range of applications. By 2020, it is expected that 31 billion IoT devices will be deployed worldwide. The rapid growth of smart devices and their reliance on wireless mechanics for data transfer have increased their vulnerability to cyberattacks. As a result, studying IoT security dangers and viable countermeasures can aid academics in discovering acceptable solutions to various cybercrime investigation challenges. In this study, various security vulnerabilities at each layer are also examined in‐depth and corrective options for smart city applications and Industry 4.0. A comparison analysis of IoT/IIoT wireless communication features and security challenges in IoT systems is also part of this study. The relevance of IoT forensics in cybercrime investigation in many areas such as smart homes, smart cities, automated cars, and healthcare is also discussed in this study. This article presents IoT security concerns and open issues, laying the groundwork for future research.